2012
DOI: 10.1039/c2cc36052g
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide/polyaniline nanostructures: transformation of 2D sheet to 1D nanotube and in situ reduction

Abstract: The formation of unique polyaniline nanotubes has been reported in presence of graphene oxide (GO) which plays crucial dual role as dopant and soft template, simultaneously. GO in nanotubes is in situ reduced to reduced GO with restoration of electrical conductivities and enhanced thermal stabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 36 publications
7
60
0
1
Order By: Relevance
“…2C). The spectrum of G/PANI exhibited almost the same vibrational bands as pure PANI, however; the deviations from the characteristic band for G/PANI at 1240, 1303, and 3206 cm À1 can be attributed to molecular interaction between graphene and PANI [25,26]. These results confirmed that PANI formed a composite particle with graphene.…”
Section: G/pani Nanocomposite Characterizationsupporting
confidence: 87%
“…2C). The spectrum of G/PANI exhibited almost the same vibrational bands as pure PANI, however; the deviations from the characteristic band for G/PANI at 1240, 1303, and 3206 cm À1 can be attributed to molecular interaction between graphene and PANI [25,26]. These results confirmed that PANI formed a composite particle with graphene.…”
Section: G/pani Nanocomposite Characterizationsupporting
confidence: 87%
“…23 The current study introduces a new strategy for the development of a free-standing hydrogel composite film consisting of polyaniline (PANi) and reduced graphene oxide sheets, where PANi plays multi-roles including reduction, crosslinking, a spacer to wedge open stacked graphene sheets, and an additive for pseudocapacitance. As noted before, GO can be partially reduced during the in situ polymerization of aniline [24][25][26] or during its contact with some conjugated polymers such as poly (m-phenylenediamine) to produce a composite through a redox reaction. 27 A dopant poly (2-acrylamido-2-methyl-1propanesulfonic acid (PAMPA) is selected for PANi because it has extraordinary stability under high oxidizing potentials and because it improves water accessibility to PANi.…”
Section: Introductionmentioning
confidence: 99%
“…a). The peaks observed at 1,720, 1,624, and 1,043 cm −1 correspond to C=O stretching, unoxidized sp 2 C‐C bonds, skeletal C‐O stretching respectively, confirming the oxidation of GO sheet . For PANI, the absorption peaks are observed at 1,546, 1,465, 1,286, and 1,230 cm −1 corresponding to the C=C quinoid, C=C benzenoid, C‐N stretching mode of the aromatic amine, C‐N‐C stretching vibration in the polaron structure , respectively as shown in Fig…”
Section: Resultsmentioning
confidence: 78%
“…The polymerization of these anilinium ions occurs beneath GO forming cylindrical aggregates to obtain GO‐wrapped PANI nanorods (Fig. ) , which are responsible for supercapacitive behavior. Thus, 10 wt% GO concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%